EFFECTIVENESS OF MEDIATION IN PREVENTING DIVORCE IN THE LAND OF PAPUA - Baitur Rohman; Mochammad Agus Rachmatulloh (Fakultas Agama Islam UNISMA, 2022)
Mediation as an alternative dispute resolution, of course, provides a fairly large maslahah value to those who are litigating. Mediation in divorce cases in the Religious Courts is a mandatory stage before the case proceeds to the trial stage. The main problem in the research, how is the effectiveness of mediation in preventing divorce in Papua. The focus of the research is on the successes and failures as well as the factors that influence the implementation of mediation at the three Religious Courts in Papua (Jayapura, Sentani and Arso). The purpose of the study was to analyze the effectiveness of mediation in preventing divorce in Tanah Papua. This type of empirical legal research is qualitative in nature with a juridical-sociological approach. Primary data sources for Judges and Registrars at the three Religious Courts. Data collection methods are observation, interviews, and documentation studies. Data analysis techniques with data reduction, data presentation and drawing conclusions. The results show the percentage of successful mediation of divorce cases over the last four years: Jayapura Religious Court 10.3%; Sentani 1.8%; and Arso 2.3%. Based on the results of these percentages, it is concluded that the role of mediation to prevent divorce in the three Religious Courts has not been effective. Factors that influence: The professionalism of judges is still low; The minimum number of mediators; and the litigants. The research implication is that so that the implementation of mediation in preventing divorce in Tanah Papua can run effectively, strategic steps must be taken, namely: Increasing the quantity and quality of mediator judges in the Religious Courts; Optimizing the role of Mediator from outside the court; Develop partnerships with BP4 in mediating and fostering sakinah families. Keywords: Effectiveness, Mediation, Divorce, Papua EFEKTIFITAS MEDIASI DALAM MENCEGAH TERJADINYA PERCERAIAN DI TANAH PAPUA Abstrak Mediasi sebagai salah satu alternatif penyelesaian sengketa, tentu memberikan nilai maslahah cukup besar terhadap mereka yang berperkara. Mediasi dalam perkara perceraian di Pengadilan Agama merupakan tahapan wajib dilaksanakan sebelum perkara dilanjutkan ke tahap persidangan. Masalah pokok dalam penelitian, bagaimana efektifitas mediasi dalam mencegah terjadinya perceraian di Tanah Papua. Fokus penelitian mengenai keberhasilan dan kegagalan serta faktor-faktor yang berpengaruh terhadap pelaksanaan mediasi pada tiga Pengadilan Agama di Papua (Jayapura, Sentani dan Arso). Tujuan penelitian untuk menganalisis efektifitas mediasi dalam mencegah terjadinya perceraian di Tanah Papua. Jenis penelitian hukum empiris, bersifat kualitatif dengan pendekatan yuridis-sosiologis. Sumber data primer Hakim dan Panitera pada tiga Pengadilan Agama tersebut. Metode pengumpulan data observasi, wawancara, dan studi dokumentasi. Teknik analisa data dengan reduksi data, penyajian data dan penarikan kesimpulan. Hasil menunjukkan prosentase keberhasilan mediasi perkara perceraian selama empat tahun terakhir: Pengadilan Agama Jayapura 10,3%; Sentani 1,8%; dan Arso 2,3%. Berdasarkan hasil prosentase tersebut, diambil kesimpulan bahwa peran mediasi untuk mencegah terjadinya perceraian di tiga Pengadilan Agama tersebut belum efektif. Faktor-faktor yang mempengaruhi: Profesionalisme hakim yang masih rendah; Minimnya jumlah mediator; dan Para pihak yang berperkara. Implikasi penelitian, agar pelaksanaan mediasi dalam mencegah terjadinya perceraian di Tanah Papua dapat berjalan dengan efektif maka harus dilakukan langkah-langkah strategis yaitu: Meningkatkan kuantitas dan kualitas para hakim mediator di Pengadilan Agama; Optimalisasi peran Mediator dari luar pengadilan; Mengembangkan kerjasama kemitraan dengan BP4 dalam melakukan mediasi dan pembinaan keluarga sakinah. Kata Kunci: Efektifitas, Mediasi, Perceraian, Papua